1994
DOI: 10.1063/1.111802
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy using a fiber optic probe with subwavelength aperture

Abstract: Raman spectroscopy with subwavelength spatial resolution of a diamond sample was recorded using a tapered fiber optical probe in conjunction with a conventional Raman spectrometer. The experiment demonstrates the potential of suboptical wavelength resolution analytical spectroscopy. The tapered fiber optical probe with an aperture of around 100 nm, served as the means for delivering pump radiation while simultaneously collecting the Stokes radiation from the diamond specimen. Comparing the magnitude of the Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…1(b)). While our focus is to apply our findings to design better type-II ABIDs, this geometry may also be of relevance to research areas, such as near field Raman scattering [18] and near field radiation force [19]. In Section 2, we will report on our experimental measurements of the collection mode point spread functions (CPSFs) (formally defined in Section 2) for different aperture sizes.…”
Section: Introductionmentioning
confidence: 99%
“…1(b)). While our focus is to apply our findings to design better type-II ABIDs, this geometry may also be of relevance to research areas, such as near field Raman scattering [18] and near field radiation force [19]. In Section 2, we will report on our experimental measurements of the collection mode point spread functions (CPSFs) (formally defined in Section 2) for different aperture sizes.…”
Section: Introductionmentioning
confidence: 99%
“…However, for practical reasons, it would be more difficult to detect the weak signals in the nanoscale since smaller apertures make the near-field signal smaller. This is crucial particularly for Raman applications since Raman scattering cross section is extremely small, which results in the use of large aperture (poor resolution) or unrealistic long acquisition time [9,10]. On the other hand, additional signal enhancement can be expected in the case of apertureless-type probes especially when the probes are made of a metal.…”
Section: Nsom Probesmentioning
confidence: 99%
“…Near-field experiments have mostly been developed and operated in the visible wavelength region [9][10][11][12][13][14][15][16][17][18][19][20]. In this wavelength range, ANSOM techniques combined with Raman and fluorescence spectroscopy are commonly used.…”
Section: Surface Plasmon Tuning In Visible Wavelengthmentioning
confidence: 99%
“…With the aid of the STM invention, scanning probe microscope technique matured, and in 1984, Pohl et al reported the fundamental technique of NSOM [4], where they used an aperture type probe coated with thin metal films. Following this, NSOM has been exploited for many applications, such as spectroscopy and optical memory, by using an aperture type probe [9,10]. The early stage of NSOM has accessed the chemical properties of samples mainly by a e-mail: yuika@ap.eng.osaka-u.ac.jp fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%